Utilization of bamboo for concrete columns in earthquake-resistant simple houses in Indonesia - Muhtar; Amri Gunasti; Adhitya Surya Manggala (Case Studies in Construction Materials, 2024)
Most simple rural houses are susceptible to earthquake damage due to their lack of reinforced concrete structures. Therefore, this research examined the use of bamboo as reinforcement for reinforced concrete columns in simple houses within rural communities. Bamboo was chosen due to its high tensile strength, sustainable, and eco-friendly properties. The research focused on investigating the seismic performance of CB columns, analyzing various aspects such as lateral load capacity, crack pattern, drift ratio, stiffness, ductility, and energy dissipation capacity. The experimental setup consisted of six CB columns with bamboo reinforcement ratios (ρb) of 4% and 6%, while a control column (CS) with a steel reinforcement ratio (ρs) of 1.4%. Each column was subjected to a constant axial load of 54.84 kN and a cyclic lateral load according to the specifications outlined in ACI 375.1–05. The test results showed that the CS column exhibited a wider hysteresis loop area, indicating greater energy dissipation than the CB columns. However, the CB column with a ρb of 6% and a stirrup spacing of 150 mm achieved a drift ratio of 3.34%, meeting the minimum requirement of 1.5% specified by ASCE standards. It also obtained an energy dissipation ratio of 0.96, meeting the ACI standard, which stipulated a minimum energy dissipation ratio of 1/8. Based on these findings, it can be concluded that CB columns, specifically those with a ρb of 6% and a stirrup spacing of 150 mm, are suitable for implementation as earthquake-resistant structural columns in simple houses within underdeveloped village areas.